2001
DOI: 10.1002/jlcr.461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tritium labeled [3R‐3H]‐, and [3S‐3H]‐L‐phenylalanine

Abstract: The synthesis of two selectively labeled isotopomers of L‐phenylalanine, (Phe), using chemical and enzymatic methods is reported. The [3R‐3H]‐L‐Phe isotopomer has been obtained from [3‐3H]cinnamic acid prepared from benzaldehyde and malonic acid using tritiated water as a source of radioactive label, and by addition of ammonia in the presence of enzyme PAL. The [3S‐3H]‐L‐Phe isotopomer has been synthesized by addition of ammonia to cinnamic acid in a buffered medium containing PAL and tritiated water. Copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The isotopomer [2‐ 14 C]‐ l ‐Phe, 2 , was obtained by the, partly similar, combined chemical and enzymatic methods using [2‐ 14 C]‐malonic acid as a source of label, Scheme . Also, the isotopomers [(3 R )‐ 3 H]‐ l ‐Phe, 3 , Scheme , and [(3 S )‐ 3 H]‐ l ‐Phe, 4 , Scheme , were synthesized by the chemical and enzymatic procedures . The doubly labeled [(3 S )‐ 2 H/ 3 H]‐ l ‐Phe, 5 , was obtained according to the Scheme by addition of ammonia to cinnamic acid carried out in fully deuteriated incubation medium containing tritiated water.…”
Section: Methodsmentioning
confidence: 99%
“…The isotopomer [2‐ 14 C]‐ l ‐Phe, 2 , was obtained by the, partly similar, combined chemical and enzymatic methods using [2‐ 14 C]‐malonic acid as a source of label, Scheme . Also, the isotopomers [(3 R )‐ 3 H]‐ l ‐Phe, 3 , Scheme , and [(3 S )‐ 3 H]‐ l ‐Phe, 4 , Scheme , were synthesized by the chemical and enzymatic procedures . The doubly labeled [(3 S )‐ 2 H/ 3 H]‐ l ‐Phe, 5 , was obtained according to the Scheme by addition of ammonia to cinnamic acid carried out in fully deuteriated incubation medium containing tritiated water.…”
Section: Methodsmentioning
confidence: 99%
“…3. Addition of ammonia to cinnamic acid, catalyzed by PAL, was carried out in the buffer containing tritiated water, HTO, leading to formation of ( 1a ) [25, 26].
Fig.
…”
Section: Synthesismentioning
confidence: 99%
“…The tritiated benzaldehyde ( 4a ) was condensed with malonic acid ( 6 ) in pyridine solvent using catalytic amounts of piperidine giving [3- 3 H]-cinnamic acid ( 2a ). Compound 2a then was converted into ( 1d ) by addition of ammonia catalyzed by PAL [25] (Fig. 4).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Final chemical conversion produced [ 14 C 4 ]everolimus.Concentration of precursor: The variation of the concentration may have a significant influence on features of the fermentation process, in particular the on incorporation (Inc), the dilution factor (Dil) and the mass yield of the metabolite 24. ADME studies of everolimus (51b), a rapamycin derivative with immunosuppressive activity, suggested that it was metabolically cleaved at two sites, indicated by hashed lines in the structure.…”
mentioning
confidence: 99%